Guidelines for Public Debt Management : Accompanying Document and Selected Case Studies. (Manuals and Guides, 2003)
This accompanying document to the Guidelines for Public Debt Management, which the IMF and the World Bank co-published in 2001, contains sample case studies that illustrate how a range of countries from around the world and at different stages of economic and financial development are developing their debt management capacity in a manner consistent with the guidelines. The experience of these countries is discussed in this publication, and should offer some useful and practical suggestions to other countries, as they strive to build their own capacity in public debt management.